Effects of vacuum packaging on the physical quality of minimally processed potatoes - Rocha, Ada M. C. N. (2011)
In recent years, consumers have become more health conscious in their food choices but they also have less time to prepare healthy meals. As a result, minimally processed (MP) products have become an important sector of the food industry because of their ‘fresh-like’ qualities, convenience and speed of meal preparation. In this study, the physical qualities of MP potatoes (‘Désirée’ variety) stored for 7 days in vacuum packaging were evaluated. The shelf life of MP potatoes was effectively extended to nearly 1 week under refrigerated storage by using vacuum packaging systems. The main quality parameters were constant during storage.